Characteristics of pelargonium radula as a mercury bioindicator for safety assessment of drinking water - Majid, Noraishah A.; Phang, Ing Chia; Darnis, Deny Susanti (Springer, 2017)
Identification of Pelargonium radula as bioindicator for mercury (Hg) detection confers a new hope for monitoring the safety of drinking water consumption. Hg, like other non- essential metals, inflicts the deterioration of biological functions in human and other creatures. In the present study, effects of Hg on the physiology and biochemical content of P. radula were undertaken to understand the occurrence of the morphological changes observed. Young leaves of P. radula were treated with different concentrations of Hg-containing solution (0.5, 1.0 and 2.0 ppb) along with controls for 4 h, prior to further analysis. Elevated Hg concentration in treatment solution significantly prompted an increased accumulation of Hg in the leaf tissues. Meanwhile, total protein, chlorophyll and low molecular mass thiol contents (cysteine, glutathione and oxidized glutathione) decreased as Hg accumulation increased. However, phyto chelatin 2 productions were induced in the treated leaves, in comparison to the control. Based on these findings, it is postu- lated that as low as 0.5 ppb of Hg interferes with the metabolic processes of plant cells, which was reflected from the morpho- logical changes exhibited on P. radula leaves—the colour of the Hg-treated leaves changed from green to yellowish-brown, be- came chlorosis and wilted. Changes in the tested characteristics of plant are closely related to the Hg-induced morphological changes on P. radula leaves, a potential bioindicator for detecting Hg in drinking water.